Feasibility Assessment of Polyethylene Terephthalate on Fresh and Hardened Traits of Blended Mortar Mixes - Rathore, Rituraj Singh; Prakash, Divya; Chouhan, Harshwardhan Singh (International Research Journal of Multidisciplinary Technovation, 2024)
Nowadays, the construction industry requires an ample quantity of non-renewable materials resulting in the excavation of natural beds and thus creating an imbalance in our environment. Besides this, plenty of waste material such as plastic waste in the forms of powder, fiber, etc. is produced daily. Sustainable disposal of this waste has appeared as a tough task across the world. The current work was undertaken to reduce the issue of plastic waste mainly polyethylene terephthalate, disposal by its effective utilization in cement mortar mixes without affecting their physical, chemical, mechanical, durability, and microstructural properties. For this, a total of ten cement mortar mixes with 1:3 and 1:6 mix proportions were prepared by using polyethylene terephthalate plastic waste [1mm (68%), 2mm (22%), 3mm (6%), and 4mm (4%)] in place of fine aggregate upto 20% replacement at an interval of 5%. These mortar mixes were evaluated for their workability, water absorption, compressive strength, flexural strength, acid attack, and shrinkage properties. Effects on internal structure were monitored by microstructural analysis such as X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy techniques. With 5% polyethylene terephthalate instead of river sand, the mixes displayed improved strength with the highest recorded 8.03 MPa and 2.36 MPa for 1:3 and 1:6 mixes respectively, and also obtained workability with increased density and homogeneity of structure. Benefits from polyethylene terephthalate were confirmed through microstructural analysis techniques except that there was a reduction in drying shrinkage. The results recommend that polyethylene terephthalate can be a reliable material in advanced construction applications offering enhanced structural parameters to save natural resources.